Antibiogram of Staphylococcus aureus isolated from clinical cases of bovine mastitis - Kaur, Jasleen; Chhabra, Rajesh; Manoj, Jinu; Singh, Mahavir (Indian Journal of Veterinary Medicine, 2024)
The present study was conducted to determine the antibiogram of Staphyloccus aureus isolates obtained from clinical cases of bovine mastitis. A total of 102 S. aureus isolated from mastitic milk samples were subjected to In vitro antibiotic sensitivity testing against 14 different antibiotics belonging to 9 different classes. The antibiotics comprised of mixture of conventionally and few non-conventionally used antibiotics. Diameters of zone of inhibitions were recorded and interpreted according to the breakpoints given by CLSI. On the basis of sensitivity pattern, isolates were categorized into multidrug-resistant (MDR), extreme drugresistant (XDR), and pandrug-resistant (PDR). Variable sensitivity with a wide range was observed against antibiotics. Antibiotic sensitivity pattern revealed maximum sensitivity towards chloramphenicol (88.24%) and maximum resistance towards vancomycin (91.18%). Out of 102 isolates, 73 (71.56%) isolates were found to be multidrug-resistant. None of the multidrug isolates were found to be extreme drug-resistant and pan drug-resistant. No relation was observed between sensitivity pattern with conventional and non conventional antibiotics.